Kidney health programs in Latin America: Results of the SLANH survey 2024 (2025)
Chronic kidney disease (CKD) is a health problem worldwide, but it is overexpressed in Latin America. With the aim of understanding the status of kidney health programs (KHP) and provide information to help create or direct kidney health policies, the Kidney Health Committee of the Latin American Society of Nephrology and Hypertension (SLANH) developed an electronic survey that was sent (February 1–May 30, 2024) to the national nephrology society, the Ministry of Health or a policymaker, and a recognized local nephrology leader of all SLANH member countries. Thirteen of 20 (65%) member countries had a KHP. Although with variability, most covers individuals with and without social security, targeting people with risk factors with or without CKD (61%) or general population (39%). In all but two countries with KHP, it is integrated into another noncommunicable disease program (diabetes, hypertension, obesity, and/or cardiovascular disease), and the national nephrology society is involved (except in three). Virtually all countries perform educative interventions for multidisciplinary health professionals and general population, the latter mainly in connection with World Kidney Day. Only eight (40%) countries have a registry of CKD stage 1-4 (seven of them had a KHP), and nine (45%) have a kidney health law, which was not different between countries with or without KHP. Only 25% of countries have active patient participation in kidney issues, regardless of the country having KHP or not. The SLANH-KHP survey showed heterogeneity in the way Latin American countries address kidney health. These findings could guide the implementation of strategies aimed at reducing the burden of CKD toward equitable and sustainable kidney disease care.